PENERAPAN ALGORITMA K-MEANS CLUSTERING PADA PENGELOMPOKKAN PASANGAN USIA SUBUR PESERTA KB DI KABUPATEN CIREBON - Rizka Amelia; Martanto Martanto; Agus Bahtiar (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2022)
One of the problems faced by newly married couples is planning the birth of children in the family. The problem of regulating the birth spacing of children in the family can be regulated by the family planning program that has been launched by the Government. One way to suppress the problem of population growth rate in Indonesia is through the KB (Family Planning) program. The success of the family planning program can be seen from the contraceptive methods used by couples of childbearing age (PUS) in each region. The main purpose of this study was to determine the best group of couples of childbearing age for family planning participants based on the contraceptives used in Cirebon Regency using the K-means algorithm, where this algorithm can solve the clustering problem in determining the best group of couples of childbearing age family planning participants. The results of the clustering process to find the best group of couples of childbearing age for family planning participants by looking for the smallest DBI value and obtained K-2 as the best group with a Davies Bouldin Index value of 0.071. The best number of clusters from the grouping of fertile age couples for family planning participants is 2 clusters, cluster 0 has 20 items members and cluster 1 has 20 items members. Keywords: Clustering, K-Means, Family planning(KB), Couples of childbearing age(PUS)